Light-induced mass transport in amorphous chalcogenides/gold nanoparticles composites - Trunov, M.L.; Lytvyn, P.M.; Nagy, P.M.; Oberemok, O.S.; Durkot, M.O.; Tarnaii, A.A.; Prokopenko, I.V.; Rubish, V.M. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2013)
We have established that mass-transport processes in two types of amorphous
materials, based on light-sensitive inorganic compounds like Se and As₂₀Se₈₀ chalcogenide
glasses (ChG), can be enhanced at the nanoscale in the presence of localized plasmonic
fields generated by visible light in gold nanoparticles (GNPs), if the condition of surface
plasmon resonance (SPR) is fulfilled. It was found that irradiation by light in the presence of
SPR produces profound surface nanostructurizations, and variation in topography follows
closely and permanently the underlying near field intensity pattern. We have proposed a
model of mass-transport in which the existence of moving anisotropic dipolar units and
internal electric field in ChG as a main driving force of this movement is suggested.